2014
DOI: 10.1007/s12975-014-0373-7
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Recombinant T Cell Receptor Ligand RTL1000 as a Therapeutic Agent in Ischemic Stroke

Abstract: Recombinant T-cell Receptor Ligand 1000 (RTL1000), a partial human major histocompatibility complex (MHC) molecule coupled to a human myelin peptide, reduces infarct size after experimental stroke in HLA-DRB1*1502 transgenic (DR2-Tg) mice. In this study, we characterized the therapeutic time window of opportunity for RTL1000; we explored the efficacy of single dose of RTL1000 administration and determined if RTL1000 affordslong-term neurobehavioral functional improvement after ischemic stroke. Male DR2-Tg mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
(43 reference statements)
2
22
0
1
Order By: Relevance
“…Recombinant T-cell receptor (TCR) ligands (RTL) are molecular constructs comprised of covalently linked α1 and β1 domains of MHC II molecules with an attached antigenic peptide (Pan et al 2014; Zhu et al 2015; Zhu et al 2014). Unlike four-domain MHC II molecules that induce T cell activation, RTLs are partial agonists of TCR and can deviate autoreactive T cell responses towards an anti-inflammatory phenotype (Burrows et al 2001; Wang et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant T-cell receptor (TCR) ligands (RTL) are molecular constructs comprised of covalently linked α1 and β1 domains of MHC II molecules with an attached antigenic peptide (Pan et al 2014; Zhu et al 2015; Zhu et al 2014). Unlike four-domain MHC II molecules that induce T cell activation, RTLs are partial agonists of TCR and can deviate autoreactive T cell responses towards an anti-inflammatory phenotype (Burrows et al 2001; Wang et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…tMCAO was induced in male C57BL/6J mice for 1 hour by reversible right MCAO under isoflurane anesthesia followed by 96 hours of reperfusion as described previously (Banerjee et al, 2013). The 96 hour time point was selected based on our previous work (Zhu et al, 2015), indicating that it is a valid time point for assessment of infarct volume by 2 ,3,5-Triphenyltetrazolium Chloride (TTC) staining post-ischemia. The investigator performing the tMCAO surgery was blinded to treatment group.…”
Section: Methodsmentioning
confidence: 99%
“…The dose and injection protocol of RTL1000 was established in our previous studies (Subramanian et al, 2009; Zhu et al, 2014A; Zhu et al, 2014B). …”
Section: Methodsmentioning
confidence: 99%
“…These findings indicate that RTL551 may not work in patients with stroke considering species-differences (murine vs. human) in antigens and MHC II molecules. To determine if a RTL strategy would work against human stroke, we determined the efficacy of humanized RTL1000, which contains a human MHC moiety (HLA-DR2) covalently linked to a human myelin peptide (hMOG-35-55) in experimental stroke in humanized DR2-Tg mice which expresses human TCR(Subramanian et al, 2009; Zhu et al, 2014A). We found that RTL1000 indeed protects against ischemic injury in young male DR2-Tg mice.…”
Section: Introductonmentioning
confidence: 99%
See 1 more Smart Citation